IMPLEMENTASI LAYANAN BIMBINGAN KELOMPOK MENGGUNAKAN TEKNIK DISKUSI BERBANTUAN APLIKASI GOOGLE MEET UNTUK PESERTA DIDIK KELAS VII DENGAN MOTIVASI BELAJAR RENDAH DI SMP BIMASENA - Kurnia, Siti; Fatimah, Siti (IKIP Siliwangi, 2024)
Learning motivation is a driving force from within students who provide encouragement and guide and maintain conscious learning activities so that learning objectives can be achieved. Learning motivation is very important in a learning process. The existence of the Covid-19 pandemic has made the learning process carried out online, ultimately affecting students' learning motivation. Group guidance on discussion techniques assisted by the Google Meet application is one way to increase students' learning motivation. Researchers used descriptive research methods with a qualitative approach to determine the implementation of group guidance services using discussion techniques for students with low learning motivation. The variable in this study is the group guidance service of discussion techniques assisted by the google meet application and the subject is class VII students of SMP Bimasena with low learning motivation. Based on the results of research using data collection methods in the form of observation and supported by interview results, it shows that group guidance services using discussion techniques with the help of the google meet application for students with low learning motivation at Bimasena Middle School can be implemented well.